"Biomanipulacja". V. Ryby drapieżne jako czynnik ograniczający zagęszczenie ryb planktonożernych - Prejs, Andrzej (Państwowe Wydawnictwo Naukowe, 1988)
Strony 295-306 ; 24 cm
Bibliografia na stronach 302-305
Streszczenie w języku angielskim
Keywords: biomanipulacja; dynamika populacji; ryby drapieżne

Ryby jako czynnik redukcji i regulacji liczebności komarów w biocenozie - Dąbrowska-Prot, Eliza (Państwowe Wydawnictwo Naukowe, 1970)
An anałysis was made of the directions in which research on the predatory activities of fish in relation to mosquitoes has developed over the last fifty years. The following problems are discussed: 1) aclimatisation of species of predatory fish new to a given area, 2) utilization of local species of fish in biological control of mosquitoes, 3) determination by ecological factors (biotic and abiotic) the intensity of the predation of fish on mosquitoes. A discussion is given under 1. and 2. of the problem of introduction into different: types of waters - artificial and natural - of exotic species of fish (in. particular the species Gambusia and Lebistes reticulatus), the adaptations of these species to different climatic conditions and the possibilities of using of the species of the local ichtiofauna in control of mosquitoes. Studies are discussed under 3. dealing with the influence on intensity of the predatory activities of fish: a) of the predator population structure (age, sexual), seasonal activity and food preferences of the predator, b) density of prey populations, c) competition among predator populations, d) habitat structure (vegetation) determining the distribution in space of prey and predator populations. In addition the problem is discussed of the indirect effect of fish on mosquitoes through transforming the habitat in a direction unfavourable to them. Attention is drawn to studies concerned with the predation of fish as a factor in biological regulation of the numbers of mosquitoes.
Strony 285-292 ; 24 cm
Streszczenie w języku angielskim
Keywords: komary; ryby drapieżne; zwalczanie biologiczne